2016
DOI: 10.1016/j.breast.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Psycho-oncological support for breast cancer patients: A brief overview of breast cancer services certification schemes and national health policies in Europe

Abstract: Psycho-oncology addresses the psychological, social, behavioural, and ethical aspects of cancer. Identification and proper management of the patients' psychosocial needs, as well as the needs of their caregivers and family are essential for a person-centred concept of breast cancer care. The aim of this overview is to describe how psychosocial support in breast cancer is incorporated in cancer-related policy documents, such as national cancer plans and breast cancer care certification schemes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“… 2 Cancer treatment is challenging because many physical and psychosocial problems are present at all stages of the disease but conventional treatment for cancer such as chemotherapy focuses on addressing the physical dimensions of cancer (ie, stopping or slowing the growth of cancer cells). 3 4 Given that QOL is a comprehensive assessment of clinical outcome, examining the level and predictors of QOL in patients with cancer is essential in developing measures to improve quality of care and treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Cancer treatment is challenging because many physical and psychosocial problems are present at all stages of the disease but conventional treatment for cancer such as chemotherapy focuses on addressing the physical dimensions of cancer (ie, stopping or slowing the growth of cancer cells). 3 4 Given that QOL is a comprehensive assessment of clinical outcome, examining the level and predictors of QOL in patients with cancer is essential in developing measures to improve quality of care and treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Even with significant improvement in the outcome of breast cancer over the last few decades, a survey conducted in 32 countries in Europe showed that only one-third of the countries had documented requirements and specific indicators for psychosocial interventions, resources they require, and educational requirements. 19 The role of psychosocial support remains crucial in treatment. "The SARS-CoV-2 pandemic had affected cancer care and service delivery around the world and we published the impact of the pandemic on psycho-oncology services separately."…”
Section: Discussionmentioning
confidence: 99%
“…European and American guidelines stress the need for the incorporation of psychological interventions in breast cancer services. 19,20 Even with significant improvement in the outcome of breast cancer over the last few decades, a survey conducted in 32 countries in Europe showed that only one-third of the countries had documented requirements and specific indicators for psychosocial interventions, resources they require, and educational requirements. 19 The role of psychosocial support remains crucial in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning cross-countries’ disparities, Eastern and Southern European countries tend to provide worse quality cancer care than Nordic countries. Neamţiu et al (2016) published a report analysing the availability and provision of psycho-oncological support in national policy documents and in breast cancer care certification schemes across 32 European countries following the recommendations of the EPAAC. As emerged by the above-mentioned report, 25 national and 4 regional cancer plans were identified, with 6 countries (i.e., Bulgaria, Croatia, Iceland, Lichtenstein, Romania, and Slovakia) not reporting any cancer plan, program or strategy regarding the implementation of psycho-oncological support, whilst the remaining 28 countries only mentioned the need for psycho-oncological support.…”
Section: Disparitiesmentioning
confidence: 99%
“…Detailed recommendations and guidelines for psycho-oncological support were reported in only 10 countries’ national plans, including Austria, Belgium, Germany, Netherlands. and Switzerland ( Neamţiu et al, 2016 ). Nonetheless, after 2016, the GCS opened its Cancer Centre Certification Programme to centres in non-German speaking countries in order to improve the quality of general and psychological cancer care within certified networks.…”
Section: Disparitiesmentioning
confidence: 99%